EXPONENTIAL STABILITY OF THE Co SEMIGROUP ASSOCIATED TO A THERMOELASTIC SYSTEM - Santiago Ayala, Yolanda Silvia (2004)
We prove that the eo semigroup, associated to athermoelastic system is analitic and exponential stable